Drosophila -catenin and E-cadherin bind to distinct regions of Drosophila Armadillo. - Pai, L.M.; Kirkpatrick, C.; Blanton, J.; Oda, H.; Takeichi, M.; Peifer, M. (Journal of Biological Chemistry, 1996)
Adherens junctions are multiprotein complexes mediating cell-cell adhesion and communication. They are organized around a transmembrane cadherin, which binds a set of cytoplasmic proteins required for adhesion and to link the complex to the actin cytoskeleton. Three components of Drosophila adherens junctions, analogous to those in vertebrates, have been identified: Armadillo (homolog of beta-catenin), Drosophila E-cadherin (DE-cadherin), and alpha-catenin. We carried out the first analysis of the interactions between these proteins using in vitro binding assays, the yeast two-hybrid system, and in vivo assays. We identified a 76-amino acid region of Armadillo that is necessary and sufficient for binding alpha-catenin and found that the N-terminal 258 amino acids of alpha-catenin interact with Armadillo. A large region of Armadillo, spanning six central Armadillo repeats, is required for DE-cadherin binding, whereas only 41 amino acids of the DE-cadherin cytoplasmic tail are sufficient for Armadillo binding. Our data complement and extend results obtained in studies of vertebrate adherens junctions, providing a foundation for understanding how junctional proteins assemble and a basis for interpreting existing mutations and creating new ones.